Maternity Experience of HIV-infected Women - I. A. Tregubenko; S. V. Vykhodtcev; A. I. Fedorova; A. A. Lukyanova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
Te results of the study of the main models of parental attitudes and vital values of 58 HIVinfected mothers having children aged 1-3 years were considered in the article.Structured interview, PARI technique were applied. Cluster analysis was performed for assessment of value and implication system of the women under study. Two leading polar nonconstructive models of parental attitudes were found: excessive emotional distancing (43%) and excessive concentration on child(42%). Correlation analysis revealed that excessive emotional distancing strategy has positive correlation with such vital values as “work” and “individual liberty” whereas excessive concentration on child strategy has positive correlation with maternity values and negative correlation with work values. Te results made it possible to determine the main tasks and targets of psychotherapeutic assistance for HIV-infected mothers with a view of protecting children’s mental health.